Empirical Analysis of the AfCFTA in the SADC Region: Evidence using the PPML Estimation Technique - Ngonidzashe Chiranga (Rescollacom (Research Collaborations Community), 2025)
The challenges that small countries in the Southern African Development Community (SADC) face towards the successful implementation of the Africa Continental Free Trade Agreement (AfCFTA) have not been adequately empirically tested to establish if there is scope for mutually beneficial trade among the countries as advocated by AfCFTA’s intra-regional trade promotion. This study employs the gravity model of trade theory. The main objective of this paper is to empirically test if there are mutual gains from intra-regional trade for small countries in the SADC region that face several political, legal, economic, and institutional challenges toward the successful implementation of AfCFTA. This study utilised a modified structural gravity model estimated using the Poisson Pseudo-Maximum-Likelihood (PPML) approach. A balanced panel data from a set of select nine SADC countries over the period 2010-2022 is used. The study finds that distance negatively and significantly affects bilateral trade. In addition, overlapping Regional Economic Community (REC) membership positively influences bilateral trade for small landlocked SADC countries and island nations that have a high trade presence in the region. However, after considering agricultural-dependent nations, overlapping REC membership has a trade-reducing impact. Furthermore, poor institutional quality at the destination country was found to reduce bilateral trade negatively and significantly which eventually increased the overall trade costs. The study recommends AfCFTA members diversify their exports and add value to their agriculture products to adequately benefit from the agreement.